Impact of Anesthesia Type on Blood Glucose in Intraoperative Diabetic Patients: A Systematic Review and Meta-Analysis Randomized Control Trial - Mixrova Sebayang, Septian; Burhan, Asmat; Susanti, Indah (Java Nursing Journal, 2023)
Background: systematic literature review investigating the impact of different anesthetics on intraoperative blood glucose levels of diabetic patients. Method: Databases including ProQuest, PubMed, ScienceDirect, and Wiley were searched for RCTs (randomized controlled trials) that examined the effects of various anesthetics on intraoperative blood glucose levels in diabetic patients. In one study, two researchers independently used eligibility criteria to examine the literature, extracted the data, and used RevMan 5.3 software to perform the meta-analysis. Results: We used trials for meta-analysis with seven randomized controlled trial overall with a total sample of 519 intraoperative diabetic patients. Compared with general anesthesia, it was found that the general anesthesia-epidural combination had superior glycemic control in intraoperative blood glucose levels, based on the meta-analysis results (SMD -1.78, 95% confidence interval [CI] -4.57 to -3.41), however epidural anesthesia did not show comparable superiority. Conclusions: Combined general-epidural anesthesia offers better glycemic control for postoperative blood sugar levels compared to general anesthesia, based on existing data.